A History of Organizational Behavior Management. Issue 1 (2nd January 2022) - Brethower, Dale M.; Dickinson, Alyce M.; Johnson, Douglas A.; Johnson, C. Merle
ABSTRACT: Organizational behavior management (OBM) arose as early behavior analysts decided to use data in earnest to make the world a better place, first through education, then workplace training, and eventually through business and industry as a whole. The historical roots of the field are traced through the lessons learned by these pioneers and how their formative experiences created the tools and techniques that are common within the discipline today. This history also created a worldview and conceptual system that continues to distinguish OBM from alternative approaches and is reflected in recent publication trends seen today. As the levels of analysis, specializations, implementations, and problems faced continue to vary and expand within organizational behavior management, the mantra of performance-based empiricism has remained as a steady and consistent guide throughout the decades.